Researcher Profile: An Interview with Jodi Letkiewicz, Ph.D. - Jodi Letkiewicz (Journal of Financial Therapy, 2015)
Jodi Letkiewicz, Ph.D., is an assistant professor of finance at York University in Toronto, Ontario. She teaches in the Certified Financial Planner® Core Curriculum program preparing undergraduate students for the Canadian CFP® certification and conducts research in several areas of personal finance and consumer decision-making, including behavioral aspects influencing the decision to seek financial help, how personality traits affect financial decision-making, and the financial state of young adults, including the impact student loans have on overall well-being and financial milestones early in their adult life. Dr. Letkiewicz’s goal is to increase financial well-being in the general public, which she hopes to accomplish through teaching, research, and community outreach.
Keywords: research; financial therapy; financial decision-making; financial well-being